The Integrity of a Disciple of Christ in Shepherding the Congregation - Poole, Ian; Park, Sarah; Wartika, Eti (STT Saint Paul Bandung, 2024)
This article highlights the importance of the shepherd as a disciple of Christ. Their existence as disciples who depend on and adhere to Christ will radiate integrity and piety that shines brightly for their congregation. The method used in this study is literature study. The results show that a disciple places themselves as a learner who clings to Jesus Christ for their relationship with God. It was also found that there is a significant relationship about the shepherd as a disciple of Christ that impacts their service to the congregation. Congregation members served view the Christ-centered example of the shepherd as encouraging them to imitate their way of life. In conclusion, the shepherd as a disciple of Christ yields the values of piety and holiness that affirm their testimony.